Manfaat Ekstrak Teh Hijau Terhadap Penurunan Berat Badan - Baharuddin Yusuf; Sukmawati A. Damiti; Agus Rohmat Hidayat (Jurnal Forum Kesehatan : Media Publikasi Kesehatan Ilmiah, 2021)
Abstract – Weight is as yet showing an increment and a medical condition around the world, not least in that frame of mind of Indonesia. Stoutness can increment the gamble of diabetes, hyperlipidemia, hypertension, and even lead to expanded chance of death. It happened on the grounds that of changes in way of life and undesirable eating examples of a specific local area, with the goal that the overabundance energy put away as fat in the body, particularly in the instinctive and subcutaneous. Weight reduction is generally finished by carrying out diet, work out, or the mix of both. Additionally, one valuable nourishment for wellbeing is tea (Camellia sinesis). Tea has been utilized as an everyday drink for millennia prior in China. Different sorts of tea have numerous medical advantages, like green tea (Green Tea). Green tea has been famous on the planet as a drink and a restorative plant for millennia prior. Varieties of regular flavonoids have been found to have great impact for wellbeing, for example, an enemy of weight impact. Catechins from green tea are polyphenolic flavonoid which has an organic capability that is wide and gainful to wellbeing. Specifically, epigallocatechin-3 gallate (EGCG) from green tea to get in shape and muscle versus fat amassing by expanding energy use and fat oxidation. As indicated by (Gilbert, 2006) by consuming 690 mg/day for a very long time catechin, can diminish the complete weight ± 3 kg, diminished midriff outline up to ± 3.3 cm, and decrease muscle versus fat ratio ± 1.5 kg.